PthA4AT, a 7.5‐repeats transcription activator‐like (TAL) effector from Xanthomonas citri ssp. citri, triggers citrus canker resistance. (5th July 2019) - Roeschlin, Roxana Andrea; Uviedo, Facundo; García, Lucila; Molina, María Celeste; Favaro, María Alejandra; Chiesa, María Amalia; Tasselli, Sabrina; Franco‐Zorrilla, José Manuel; Forment, Javier; Gadea, José; Marano, María Rosa
Summary: Transcription activator‐like effectors (TALEs) are important effectors of Xanthomonas spp. that manipulate the transcriptome of the host plant, conferring susceptibility or resistance to bacterial infection. Xanthomonas citri ssp. citri variant A T ( X. citri A T ) triggers a host‐specific hypersensitive response (HR) that suppresses citrus canker development. However, the bacterial effector that elicits this process is unknown. In this study, we show that a 7.5‐repeat TALE is responsible for triggering the HR. PthA4 AT was identified within the pthA repertoire of X. citri A T followed by assay of the effects on different hosts. The mode of action of PthA4 AT was characterized using protein‐binding microarrays and testing the effects of deletion of the nuclear localization signals and activation domain on plant responses. PthA4 AT is able to bind DNA and activate transcription in an effector binding element‐dependent manner. Moreover, HR requires PthA4 AT nuclear localization, suggesting the activation of executor resistance ( R ) genes in host and non‐host plants. This is the first case where a TALE of unusually short length performs a biological function by means of its repeat domain, indicating that the action of these effectors to reprogramme the host transcriptome following nuclear localization is not limited to 'classical' TALEs.